2020
DOI: 10.1590/1808-057x201910370
|View full text |Cite
|
Sign up to set email alerts
|

Behold the best and worst of me: the impostor phenomenon and academic behavior in the business area,

Abstract: The aim of this study was to analyze the relationship between the impostor phenomenon (IP) and the academic behavior of stricto sensu postgraduate students in business area courses. Discussing the relationship between psychological variables and student academic behavior is a topic of interest as empirical evidence indicates that these variables affect the environment in which scientific research is developed. It is important to look for elements that help in understanding the IP in order to reduce its impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(79 reference statements)
0
6
0
6
Order By: Relevance
“…Moreover, as they realize that their academic career may not be successful, they gradually lose their academic aspiration and adopt behaviors that are contrary to university expectations. A study by the Centre for Excellence in Teaching and Learning at the University of Waterloo (2016) found that graduate students with IP tend to have less contact with other students, struggle to effectively perform their duties as teaching assistants, and are less involved in practical activities, which can hinder their competence ( Meurer and Costa, 2020 ). These characteristics can be used as indicators of impostor among doctoral students.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as they realize that their academic career may not be successful, they gradually lose their academic aspiration and adopt behaviors that are contrary to university expectations. A study by the Centre for Excellence in Teaching and Learning at the University of Waterloo (2016) found that graduate students with IP tend to have less contact with other students, struggle to effectively perform their duties as teaching assistants, and are less involved in practical activities, which can hinder their competence ( Meurer and Costa, 2020 ). These characteristics can be used as indicators of impostor among doctoral students.…”
Section: Resultsmentioning
confidence: 99%
“…Pessoas com essas características tendem a atribuir seu sucesso à sorte, ao acaso ou a fatores alheios a sua própria competência. Para justificar suas falhas e evitar julgamentos, alunos com maiores níveis de fenômeno impostor podem moldar seu comportamento acadêmico realizando atitudes de autossabotagem (Meurer & Costa, 2020).…”
Section: Autossabotagemunclassified
“…The available research on graduate students is recent and concentrated in specific fields of knowledge, such as Health (Ferreira et al, 2015;Morrayre, 2013;Louzada;Silva Filho, 2005;Mendes;Venceslau;Aires;Prado Júnior, 2010;Teixeira et al, 2017;Viniegra et al, 2019); Sciences, Technology, Engineering, and Mathematics (STEM) (Crede, 2011;Head et al, 2021;Maclachlan, 2006;Mendes, 2017;Velho, 2012); Education (Abramowicz et al, 2009); Law (Marks;Moss, 2016); and Administration (Mccray;Joseph-Richard, 2021;Meurer;Costa, 2020;Tenorio, 2020;Stewart Williamson;King Junior, 2017). One can list at least three predominant themes in these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oliveira and Tenório (2020), in research with 629 graduates of private higher education institutions in Rio de Janeiro and Belo Horizonte, found that most graduates were male (70%), with a mean age of 37 years old, and, among the masters, 57% had previously done specialization courses. Meurer and Costa (2020) conducted a nationwide study with 1,816 business students, with 51% female, 70% White, and 52% aged up to 33 years old.…”
Section: Profile Of Graduate Studentsmentioning
confidence: 99%